2014
DOI: 10.1093/ntr/ntu038
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Regulatory Science: Research to Inform Regulatory Action at the Food and Drug Administration’s Center for Tobacco Products

Abstract: The U.S. Food and Drug Administration (FDA) promotes the development of regulatory science to ensure that a strong evidence base informs all of its regulatory activities related to the manufacture, marketing, and distribution of tobacco products as well as public education about tobacco product constituents and effects. Toward that end, the FDA's Center for Tobacco Products (CTP) provides funding for research studies with scientific aims that fall within its defined regulatory authority. However, given their t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 17 publications
0
58
0
1
Order By: Relevance
“…Legal challenges by the tobacco industry eventually led the town to rescind the law. The success of overcoming legal challenges and implementing any TCA-driven advertising regulations at POS is dependent, in part, on the extent to which a given regulatory approach is supported by the empirical literature 23. The results of the current study provide evidence that could help to inform regulatory decisions at POS for the FDA-CTP.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Legal challenges by the tobacco industry eventually led the town to rescind the law. The success of overcoming legal challenges and implementing any TCA-driven advertising regulations at POS is dependent, in part, on the extent to which a given regulatory approach is supported by the empirical literature 23. The results of the current study provide evidence that could help to inform regulatory decisions at POS for the FDA-CTP.…”
Section: Discussionmentioning
confidence: 79%
“…Adolescents were the focus of this study because they are particularly vulnerable to tobacco advertising22 and are a focus of tobacco regulatory efforts in the USA 23. The recruitment ads contained no information about smoking or tobacco in order to reduce potential sample biases and simply indicated that the study focused on teens’ purchasing habits at convenience stores.…”
Section: Methodsmentioning
confidence: 99%
“…5 As used in this paper, TRS refers to research intended to inform the FDA's regulation of tobacco. Notably, some important tobacco regulatory activitiessuch as enacting tobacco taxes or clean indoor air laws-are outside the authority of the FDA and are left to Congress or state and local governments.…”
Section: Introductionmentioning
confidence: 99%
“…8 The U.S. Food and Drug Administration (FDA) acquired regulatory authority over tobacco products in 2009, with the enactment of the Family Smoking Prevention and Tobacco Control Act. 9 One of the top priorities of the FDA's Center for Tobacco Products is to fund research studies that examine the effects of reducing the nicotine content of cigarettes, 10 which has been proposed as a means of reducing tobacco dependence in the United States). 11,12 This regulatory strategy could be particularly beneficial to smokers, such as SS, who have difficulty accessing effective smoking cessation treatments.…”
Section: Introductionmentioning
confidence: 99%